An optimization model for power grid fortification to maximize attack immunity. (July 2018) - Costa, Alberto; Georgiadis, Dionysios; Ng, Tsan Sheng; Sim, Melvyn
Highlights: The problem of power grid fortification against malicious attacks is investigated. A novel trilevel optimization model of the problem is presented. An iterative algorithm to find the optimal solution is proposed. The tradeoff between robustness and performance is analyzed for some IEEE test cases. Abstract: This paper studies the problem of allocating fortification resources in an electric power grid with the aim of maximizing its immunity against malicious attacks. An attacker of the grid allocates his attack resource budget to destroy targeted transmission lines in the network. The attacker is successful if the power load shed after attack exceeds a specified permissible level. On the other hand, the grid defender allocates his fortification budget to the lines in a manner to deter as many such attacks as possible, in particular to maximize the budget required by the attacker to be successful. This is termed as the attack immunity in our work. We formulate this as a two-stage optimization problem that generalizes several of other network fortification problems and propose an exact algorithm for its solution. Numerical studies are performed using test instances from the literature. A graphical representation of the results is also proposed as a tool for analyzing the immunity of power grids under malicious attacks.